Biology in the Dry Seed: Transcriptome Changes Associated with Dry Seed Dormancy and Dormancy Loss in the Arabidopsis GA-Insensitive sleepy1-2 Mutant - Nelson, Sven K.; Ariizumi, Tohru; Steber, Camille M. (Frontiers in Plant Science, 2017)
Plant embryos can survive years in a desiccated, quiescent state within seeds. In many species, seeds are dormant and unable to germinate at maturity. They acquire the capacity to germinate through a period of dry storage called after-ripening (AR), a biological process that occurs at 5–15% moisture when most metabolic processes cease. Because stored transcripts are among the first proteins translated upon water uptake, they likely impact germination potential. Transcriptome changes associated with the increased seed dormancy of the GA-insensitive sly1-2 mutant, and with dormancy loss through long sly1-2 after-ripening (19 months) were characterized in dry seeds. The SLY1 gene was needed for proper down-regulation of translation-associated genes in mature dry seeds, and for AR up-regulation of these genes in germinating seeds. Thus, sly1-2 seed dormancy may result partly from failure to properly regulate protein translation, and partly from observed differences in transcription factor mRNA levels. Two positive regulators of seed dormancy, DELLA GAI (GA-INSENSITIVE) and the histone deacetylase HDA6/SIL1 (MODIFIERS OF SILENCING1) were strongly AR-down-regulated. These transcriptional changes appeared to be functionally relevant since loss of GAI function and application of a histone deacetylase inhibitor led to decreased sly1-2 seed dormancy. Thus, after-ripening may increase germination potential over time by reducing dormancy-promoting stored transcript levels. Differences in transcript accumulation with after-ripening correlated to differences in transcript stability, such that stable mRNAs appeared AR-up-regulated, and unstable transcripts AR-down-regulated. Thus, relative transcript levels may change with dry after-ripening partly as a consequence of differences in mRNA turnover.